Two similar near-infrared (IR) absorbing benzannulated AZA-bodipy dyes as near-ir sensitizers for ternary solar cells - Min, Jie; Ameri, Tayebeh; Gresser, Roland; Lorenz-Rothe, Melanie; Baran, Derya; Troeger, Anna; Sgobba, Vito; Leo, Karl; Riede, Moritz; Guldi, Dirk Michael; Brabec, Christoph (ACS Applied Materials and Interfaces, 2013)
Ternary composite inverted organic solar cells based on poly(3-hexylthiophen-2,5-diyl) (P3HT) and phenyl-C-butyric acid methyl ester (PCBM) blended with two different near-infrared absorbing benzannulated aza-BODIPY dyes, difluoro-bora-bis-(1-phenyl-indoyl)-azamethine (1) or difluoro-bora-bis-(1-(5-methylthiophen)-indoyl)-azamethine (2), were constructed and characterized. The amount of these two aza-BODIPY dyes, within the P3HT and PCBM matrix, was systematically varied, and the characteristics of the respective devices were recorded. Although the addition of both aza-BODIPY dyes enhanced the absorption of the blends, only the addition of 1 improved the overall power conversion efficiency (PCE) in the near-infrared (IR) region. The present work paves the way for the integration of near-infrared absorbing aza-BODIPY derivatives as sensitizers in ternary composite solar cells. © 2013 American Chemical Society.